Drought Monitoring and assessment using earth observation data for Zambia - Amarnath, Giriraj; Alahacoon, Niranga (International Water Management Institute, 2022)
This study attempts to identify the spatial-temporal extent of the agricultural drought in Zambia using remote sensing data and crop production. IDSI is superior in terms of its performance and drought detection capability and is characterized by better representation of drought severity. Also VCI, IDSI and SPI indices were found to be very useful in monitoring the spatial-temporal extent of agricultural and climatic drought in the country. To validate the VCI and SPI based estimates, the correlation between VCI-CYA and SPI-CYA was analyzed and shown to have a strong positive correlation r2 0.72 and 0.68 respectively. The findings of drought hazard analysis could prove to be extremely useful in promoting integrated drought risk management strategies to mitigate the potential impact of drought on the agricultural sector and accelerate adaptation actions. In addition, it provides a robust foundation for decision-makers to recommend disaster preparedness and mitigation measures to minimize the effects of future droughts.